Editorial - Hayes, Grahame (PINS-Psychology in Society, 2026)
The African renaissance is upon us, and whether one reads it as ideas or attempts at economic revival, one cannot escape the reality which has been created within its purview. There are many responses to the idea of an African renaissance being put forward by the ANC government, and especially as espoused by Deputy President Thabo Mbeki. The responses vary from uncritical championing of everything African, with too little debate about what the notion of "African" might designate, to suggestions that the African renaissance is merely a thinly disguised affirmative action programme. In some quarters the African renaissance is viewed as synonymous with Afrocentrism, and implicitly, if not explicitly, an attack on everything Eurocentric. On the other hand, it is seen by some as an attempt to encourage and entrench democratic governments on the continent that will at last try to alleviate the economic hardships suffered by millions of their citizens. In short, the idea of the African renaissance can either be seen in reactionary terms as racist, or as an invitation to participate in the debate and creation of a non-racial, democratic society.